Ethical Issues in Deep Brain Stimulation - Schermer, Maartje (Frontiers in Integrative Neuroscience, 2011)
Deep brain stimulation (DBS) is currently used to treat neurological disorders like Parkinson’s disease (PD), essential tremor and dystonia, and is explored as an experimental treatment for psychiatric disorders like Major Depression (MD) and Obsessive Compulsive Disorder (OCD). This mini review discusses ethical issues in DBS treatment and research, as they have been discussed in the medical and ethical literature. With regard to DBS treatment, the most important issues are balancing risks and benefits and ensuring respect for the autonomous wish of the patient. This implies special attention to patient selection, psycho-social impact of treatment, effects on personal identity, and treatment of children. Moreover, it implies a careful informed consent process in which unrealistic expectations of patients and their families are addressed and in which special attention is given to competence. In the context of research, the fundamental ethical challenge is to promote high-quality scientific research in the interest of future patients, while at the same time safeguarding the rights and interests of vulnerable research subjects. Several guidelines have been proposed to ensure this. One of the preconditions to further development of responsible and transparent research practices is the establishment of a comprehensive registry.